Long-term general and cardiovascular safety of tiotropium/olodaterol in patients with moderate to very severe chronic obstructive pulmonary disease. (January 2017) - Buhl, Roland; Magder, Sheldon; Bothner, Ulrich; Tetzlaff, Kay; Voß, Florian; Loaiza, Lazaro; Vogelmeier, Claus F.; McGarvey, Lorcan
Abstract: Background: Long-term safety, particularly cardiovascular safety, is of special interest in maintenance treatment of chronic obstructive pulmonary disease (COPD) with long-acting β2 -agonists and long-acting muscarinic antagonists, given potential cardiovascular effects. Methods: Two 52-week Phase III trials (TONADO ® ) investigated tiotropium/olodaterol (5/5 and 2.5/5 μg) versus tiotropium 2.5, 5 μg and olodaterol 5 μg. In a pre-specified safety analysis, investigator-reported treatment-emergent adverse events (AEs), electrocardiogram and laboratory data were pooled. All serious AE (SAE) reports were reviewed by an independent Adjudication Committee, which assessed whether deaths, hospitalisations or intubations were respiratory, cardiovascular, cerebrovascular or other disease related. Subgroup analyses investigated cardiovascular safety including major cardiac events in patients with cardiovascular co-morbidities. Results: This analysis comprised 3100 patients with moderate to very severe COPD, treated for ≤1 year, including 784 patients with cardiovascular co-morbidities. AEs were balanced across treatments in the total population as well as in patient subgroups with pre-existing cardiovascular co-morbidities. The incidence and nature of events were consistent with the disease under study and a 1-year trial duration. 494/3100 patients contributed to an adjudicated analysis of SAEs: 260 had respiratory-related, 53 had cardiovascular-related and 16 had cerebrovascular-related SAEs. Incidences of these SAEs were comparable between treatments. There was no evidence of any increased risk for the combination compared to the monotherapy groups. Conclusions: These data provide confidence for clinicians that tiotropium/olodaterol 5/5 μg can be safely administered once-daily to patients with moderate to very severe COPD long-term, including those with significant cardiovascular co-morbidity. Trial registry: ClinicalTrials.gov, Nos.: NCT01431274, NCT01431287. Highlights: Two placebo-controlled 1-year studies of tiotropium/olodaterol, combined (5/5 µg and 2.5/5 µg) vs monotherapies, in COPD. 3100 patients with moderate to very severe COPD, including 784 patients with cardiovascular co-morbidities, were included. AEs were balanced across treatments in the total population and in patient subgroups with cardiovascular co-morbidities. Independent, adjudicated SAEs analysis in 494/3100 patients: 260 (respiratory), 53 (cardiovascular), 16 (cerebrovascular). SAE incidences were comparable between treatments: there was no evidence of increased risk for combination vs monotherapy.